Acetyl-l-carnitine Administration Increases Insulin-like Growth Factor 1 Levels in Asymptomatic HIV-1-Infected Subjects: Correlation with Its Suppressive Effect on Lymphocyte Apoptosis and Ceramide Generation - Di Marzio, Luisa; Moretti, Sonia; D'Alò, Simona; Zazzeroni, Francesca; Marcellini, Sonia; Smacchia, Camillo; Alesse, Edoardo; Cifone, M.Grazia; De Simone, Claudio (Clinical immunology (Orlando, Fla.), 1999)
The aim of this study was to investigate the impact of long-term acetyl-L-carnitine administration on CD4 and CD8 absolute counts, apoptosis, and insulin-like growth factor-1 (IGF-1) serum levels in HIV-1-infected subjects. The generation of cell-associated ceramide and HIV-1 viremia were also investigated. Eleven asymptomatic, HIV-1-infected subjects were treated daily with acetyl-L-carnitine (3 g) for 5 months. Immunologic and virologic measures and safety were monitored at the start of the treatment and then on days 90 and 150. Altogether our findings suggest that acetyl-L-carnitine administration has a substantial impact on the main immunologic abnormality associated with HIV infection, the loss of CD4 cells, by reducing the rate of apoptotic lymphocyte death. The reduction of ceramide generation and the increase of the serum levels of IGF-1, a major survival factor able to protect cells from apoptosis by different stimuli and conditions, could represent two important mechanisms underlying the observed anti-apoptotic effects of acetyl-L-carnitine.